First report of Colletotrichum siamense causing leaf spot on Machilus pauhoi in China - Lv, Baishuan (Plant disease, 2022)
Machilus pauhoi Kaneh. is an excellent evergreen broad-leaved tree species widely grown in China for its ornamental and economic value (He et al. 2022). In September 2021, a leaf spot was observed on M. pauhoi plants on Guantian forest farm (27°06'15.6″N, 114°34'20.72″E) in ji' an city, Jiangxi province, China. The disease incidence was estimated to be above 20%. The symptoms began as brown irregular spots, then the spots gradually expand over time, with a gray-to-brown center and dark brown-to-black edges. Small infected tissues (3 to 5 mm2) were surface-sterilized in 70% ethanol for 30 s and 2% NaClO for 60 s, and rinsed three times with sterile water (Ju et al. 2021). Tissues were placed on potato dextrose agar (PDA) and incubated at 25°C. Pure cultures were obtained by transferring hyphal tips to new PDA plates. Twenty-two isolates of Colletotrichum ssp. were obtained (isolation frequency about 78%). Three representative single-spore isolates (PN-1, PN-4, and PN-9) were used for morphological studies and phylogenetic analyses. Colonies on the PDA of the three isolates were white to gray with cottony mycelia and grayish-white on the undersides of the culture. Conidia were single-celled, straight, hyaline, cylindrical, clavate, and measured 11.4-16.8 ×4.1-5.5 µm (13.2 ± 1.0 × 4.4 ± 0.3 µm, n = 100). Appressoria were brown to dark brown, ovoid to clavate, slightly irregular to irregular, and ranged from 5.2-8.8 × 4.1-6.2 µm (6.7 ± 0.2 × 5.1 ± 0.3 µm, n=100). Morphological features were similar to Colletotrichum gloeosporioides species complex (Weir et al. 2012). The internal transcribed spacer (ITS) regions, actin (ACT), calmodulin (CAL), beta-tubulin 2 (TUB2), chitin synthase (CHS-1), and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) were amplified from genomic DNA for the three isolates using primers ITS1/ITS4, ACT-512F/ACT-783R, CL1/CL2, T1/Bt2b, CHS-79F/CHS-354R and GDF/GDR (Weir et al. 2012), respectively. All sequences were deposited into GenBank (ITS, ON176154 - ON176156; ACT, ON185554 - ON185556; GAPDH, ON185563 - ON185565; TUB2, ON185566 - ON185568; CHS-1, ON185560 - ON185562; CAL, ON185557 - ON185559). A maximum likelihood and Bayesian posterior probability analyses using IQtree v. 1.6.8 and Mr. Bayes v. 3.2.6 with the concatenated sequences placed PN-1, PN-4, and PN-9 in the clade of C. siamense. Based on the multi-locus phylogeny and morphology, three isolates were identified as C. siamense. The pathogenicity of three isolates was tested on nine M. pauhoi plants, which were grown in the field. Healthy leaves were wounded with a sterile needle and inoculated with 10 µL of spore suspension (106 conidia/mL). The spore suspension of each isolate was inoculated onto six leaves. Another three plants inoculated with ddH2O served as the control (Wan et al. 2022). All the inoculated leaves were covered with plastic bags to keep them moist for 2 days (relative humidity > 80%). All the inoculated leaves showed similar symptoms to those observed in the field, whereas control leaves were asymptomatic for 7 days. C. siamense was reisolated from the lesions, whereas no fungus was isolated from control leaves. Up to now, Pestalotiopsis chamaeropis, Corynespora cassiicola and Arthrinium arundinis could infect M. pauhoi plants (Zhang et al. 2021), and cause leaf spots in China. To our knowledge, this is the first report of C. siamense causing leaf spots on M. pauhoi. This work provided crucial information for epidemiologic studies and appropriate control strategies for this newly emerging disease